Acoustic Detection of Krill Scattering Layer in the Terra Nova Bay Polynya, Antarctica - Kang, Myounghee; Fajaryanti, Rina; Son, Wuju; Kim, Jeong-Hoon; La, Hyoung Sul (Frontiers in Marine Science, 2020)
Krill play a crucial role in the transfer of energy in the marine food web, connecting primary producers and the upper trophic levels in the Terra Nova Bay polynya (TNBP), which is part of the Ross Sea marine protected area. Despite the substantial ecological importance of krill, there are few studies on their distribution and abundance in the TNBP. An acoustic survey was conducted on 7‒14 January 2019 in the TNBP, Ross Sea, using a Simrad EK60 echosounder (38 and 120 kHz) aboard the icebreaker RV Araon. The most commonly used range of the difference of the mean volume backscattering strength (2–16 dB) was applied to distinguish krill. The acoustic data (120 kHz) were extracted to examine the krill distribution characteristics. The study area was divided into low-value areas and high-value areas based on the third quartile of the nautical area scattering coefficient. The results showed that the krill aggregations were distributed in three layers at depths of 0‒30 m, 70‒110 m, and 270‒300 m. The interpolated environmental parameters associated with the backscattering strength were compared. High-value areas of krill coincided with relatively low temperature, low salinity, and high chlorophyll, although very weak correlations were found. The primary goal of this study was to understand the vertical and horizontal distributions of krill acoustic biomass and to relate the observed patterns to the dominant environmental conditions.